2011
DOI: 10.1111/j.1365-2885.2011.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of oral meloxicam in ruminant and preruminant calves

Abstract: The pharmacokinetics of oral meloxicam has been studied in ruminant, but not preruminant calves. Oral meloxicam was administered at 0.5 mg/kg to six ruminant calves via gavage (RG); to six preruminant calves via gavage (PRG); and to six preruminant calves via suckling in milk replacer (PRF). Plasma drug concentrations, determined over 120-h postadministration, were analyzed by compartmental and noncompartmental methods. The rate of drug absorption was faster (P<0.01) in PRF (0.237±0.0478/h) than RG calves (0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 19 publications
6
43
2
Order By: Relevance
“…However, there may be a need to administer the oral dose prior to painful procedures because previous studies that have recorded the pharmacokinetics of orally administered NSAIDs have found that they take longer to reach their maximum concentrations than when administered intravenously. 23,26,34 From the current study results, it appears that, when given orally at double the standard dose, carprofen and flunixin should be administered 2 h before sheep undergo painful procedures to allow the NSAIDs to be present at the putative therapeutic dose levels. Although carprofen maintained high concentrations in plasma 24 h following administration, both flunixin and ketoprofen had dropped to concentrations <0.1 μg/mL by this time.…”
Section: Discussionmentioning
confidence: 88%
“…However, there may be a need to administer the oral dose prior to painful procedures because previous studies that have recorded the pharmacokinetics of orally administered NSAIDs have found that they take longer to reach their maximum concentrations than when administered intravenously. 23,26,34 From the current study results, it appears that, when given orally at double the standard dose, carprofen and flunixin should be administered 2 h before sheep undergo painful procedures to allow the NSAIDs to be present at the putative therapeutic dose levels. Although carprofen maintained high concentrations in plasma 24 h following administration, both flunixin and ketoprofen had dropped to concentrations <0.1 μg/mL by this time.…”
Section: Discussionmentioning
confidence: 88%
“…Evaluation of meloxicam revealed that a mean CMAX of 1.9 μg/mL (range 1.3–2.1 μg/mL) occurred approximately 24 h (range 12–24 h) following oral administration. The mean TMAX in the present study is longer than those previously reported, and lower mean AUC values were observed (Coetzee et al ., , ; Mosher et al ., ). In the previously mentioned studies, the method of oral administration was a suspension of crushed tablets in water, whereas in our study, meloxicam tablets were administered whole and placed in a bolus filled with whey powder.…”
Section: Discussionmentioning
confidence: 97%
“…Mosher et al . () demonstrated differences in half‐life when comparing preruminant calves and ruminant calves administered meloxicam by gavage (preruminant calves dosed via gavage: T½ λ z 40.0 h; ruminant claves dosed via gavage: T½ λ z 29.9 h). In addition, breed or strain differences may also contribute due to genetic differences (polymorphisms) in metabolism, but to the authors' knowledge, genetic polymorphisms or extensive studies of the effects of age on drug metabolism in pigs have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the optimal dose regimen for pain management, the pharmacokinetics of a drug must be determined. Pharmacokinetic (PK) parameters for meloxicam have been evaluated in several species including cattle (Coetzee et al, 2009;Mosher et al, 2012;Malreddy et al, 2013), small ruminants (Shukla et al, 2007;Ingvast-Larsson et al, 2010;Kreuder et al, 2012;Wasfi et al, 2012;Stock et al, 2013), horses (Toutain et al, 2004;Sinclair et al, 2006), exotics (Divers et al, 2010), and companion animals (Lehr et al, 2010;Lees et al, 2013). There have been two peer-reviewed articles published on meloxicam PK in swine (Fosse et al, 2008(Fosse et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%